Relational Almost (ϕ,ψ)-Contractions and Applications to Nonlinear Fredholm Integral Equations - Fahad M. Alamrani; Ebrahem A. Algehyne; Esmail Alshaban; Adel Alatawi; Hamid I. A. Mohammed; Faizan Ahmad Khan (Axioms)
This paper deals with the fixed-point findings under relational strict almost <semantics>(ϕ,ψ)</semantics>-contraction. Our findings complement and strengthen prevailing results. In the course of the procedure, we also derive a related fixed point theorem for strict almost <semantics>(ϕ,ψ)</semantics>-contraction. We provide several illustrative examples to support the validity of our outcomes. We also argue about the possibility of a unique solution of a nonlinear Fredholm integral equation via our outcomes.